2022
DOI: 10.1021/acs.macromol.2c00589
|View full text |Cite
|
Sign up to set email alerts
|

Swelling and Residual Bond Orientations of Polymer Model Gels: The Entanglement-Free Limit

Abstract: We investigate the swelling of polymer model networks prepared at different polymer volume fractions and in solvents of different quality. We extend the existing theory to describe residual bond orientations (the vector and the tensor order parameters) for theta, good, and athermal solvents and put these relations in context with modulus at preparation conditions and the equilibrium degree of swelling. We find good agreement with the assumption of affine swelling for the weakly entangled networks of our study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(64 citation statements)
references
References 78 publications
6
58
0
Order By: Relevance
“…A simulation study reported exponents increasing from −0.25 to −0.55 with increasing length of still quite short chains . In contrast to this, we found only a very weak increase of the exponent for increasing N . Altogether, the dependence on ϕ 0 has not been settled yet, but this open question could be advanced by using network architectures as ours that are less susceptible to network defects.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…A simulation study reported exponents increasing from −0.25 to −0.55 with increasing length of still quite short chains . In contrast to this, we found only a very weak increase of the exponent for increasing N . Altogether, the dependence on ϕ 0 has not been settled yet, but this open question could be advanced by using network architectures as ours that are less susceptible to network defects.…”
Section: Resultsmentioning
confidence: 65%
“…In a subsequent simulation, a series of gels prepared at a broader range of concentrations were swollen to equilibrium, and the equilibrium degree of swelling was determined from the average polymer volume fraction inside the swollen gel. More details on the simulations with a particular focus on equilibrium swelling properties and the residual bond orientations are available in ref .…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…But since c i decays quickly as a function of Z, see equation ( 1), we expect that the shortest path still dominates the true return probability. Besides these corrections, there is an effective repulsion between f -functional star polymers in a melt of the same star polymers that affects the average strand size in a network 45 . Altogether, we expect that equation ( 1…”
Section: Basic Definitions For Simulations and Modelingmentioning
confidence: 99%
“…Our interest in tetra-PCL-b-PEG micelles stems from investigations on model amphiphilic co-networks based on tetra-arm PEG and PCL star polymers. [23][24][25] Here, soluble amphiphilic star block copolymers containing the same building blocks are needed to structure the material prior to network formation.…”
Section: Introductionmentioning
confidence: 99%